Landslide Susceptibility Mapping Using the Weight of Evidence Model: A Case Study on A Tropical Volcanic Region - Nugraha, Dimas Hastama; Wilopo, Wahyu; Fathani, Teuku Faisal (Pandawa Institute, 2026)
Landslides are one of the major hazards in volcanic areas, causing loss of life, property damage, and degradation of the environment. The western slopes of Mount Lawu, a stratovolcano in Central Java Province, Indonesia, are especially prone to landslides because of steep topography and increasing human activities. The rapid population growth and land use changes, driven by tourism and agricultural expansion, have increased the vulnerability of the area. This study examines the performance of the weight of evidence (WoE) method in mapping landslide susceptibility over the western slopes of Mount Lawu, with a focus on the interaction between environmental factors and land use. The parameters considered in this research include slope, lithology, distance from lineaments, roads, and rivers, rainfall, and land use. The spatial datasets used included a digital elevation model (DEM) at a scale of 1:16,000, as well as slope, river, lineament, and land-use data at a scale of 1:25,000, and lithology data at a scale of 1:50,000. All of these datasets were processed and analyzed using ArcGIS Pro. The WoE analysis resulted in the landslide susceptibility map, which divided susceptibility into four classes: high, moderate, low, and very low. The model achieved an accuracy of 0.81, demonstrating strong predictive capability. The landslide susceptibility map showed high-risk zones along steep slopes, near rivers, and close to roads, particularly in northern Ngargoyoso and western-southern Tawangmangu Districts. These results highlight the utility of the WoE method for developing the landslide susceptibility map with good accuracy. A landslide susceptibility map can be used to evaluate existing land use and to create spatial planning-based landslide disaster risk reduction.